ET-1 as a Sex-Specific Mechanism Impacting Age-Related Changes in Vascular Function - Kuczmarski, Andrew V.; Welti, Laura M.; Moreau, Kerrie L.; Wenner, Megan M. (Frontiers in Aging, 2021)
Aging is a primary risk factor for cardiovascular disease (CVD), which is the leading cause of death in developed countries. Globally, the population of adults over the age of 60 is expected to double by the year 2050. CVD prevalence and mortality rates differ between men and women as they age in part due to sex-specific mechanisms impacting the biological processes of aging. Measures of vascular function offer key insights into cardiovascular health. Changes in vascular function precede changes in CVD prevalence rates in men and women and with aging. A key mechanism underlying these changes in vascular function is the endothelin (ET) system. Studies have demonstrated sex and sex hormone effects on endothelin-1 (ET-1), and its receptors ETA and ETB. However, with aging there is a dysregulation of this system resulting in an imbalance between vasodilation and vasoconstriction. Thus, ET-1 may play a role in the sex differences observed with vascular aging. While most research has been conducted in pre-clinical animal models, we describe more recent translational data in humans showing that the ET system is an important regulator of vascular dysfunction with aging and acts through sex-specific ET receptor mechanisms. In this review, we present translational evidence (cell, tissue, animal, and human) that the ET system is a key mechanism regulating sex-specific changes in vascular function with aging, along with therapeutic interventions to reduce ET-mediated vascular dysfunction associated with aging. More knowledge on the factors responsible for the sex differences with vascular aging allow for optimized therapeutic strategies to attenuate CVD risk in the expanding aging population.